Impact of rest-redistribution on fatigue during maximal eccentric knee extensions - Merrigan, J. J.; Jones, M. T.; Padecky, J.; Malecek, J.; Omcirk, D.; Scott, B. R.; Tufano, J. J. (Journal of Human Kinetics, 2020)
Redistributing long inter-set rest intervals into shorter but more frequent rest intervals generally maintains concentric performance, possibly due to improved energy store maintenance. However, eccentric actions require less energy than concentric actions, meaning that shorter but more frequent sets may not affect eccentric actions to the same degree as concentric actions. Considering the increased popularity of eccentric exercise, the current study evaluated the effects of redistributing long inter-set rest periods into shorter but more frequent rest periods during eccentric only knee extensions. Eleven resistance-trained men performed 40 isokinetic unilateral knee extensions at 60°·s-1 with 285 s of total rest using traditional sets (TS; 4 sets of 10 with 95 s inter-set rest) and rest-redistribution (RR; 20 sets of 2 with 15 s inter-set rest). Before and during exercise, muscle oxygenation was measured via near-infrared spectroscopy, and rating of perceived exertion (RPE) was recorded after every 10th repetition. There were no differences between protocols for peak torque (RR, 241.58±47.20 N; TS, 231.64±48.87 N; p=0.396) or total work (RR, 215.26±41.47 J; TS, 209.71±36.02 J; p=0.601), but moderate to large effect sizes existed in later repetitions (6,8,10) with greater peak torque during RR (d=0.66-1.19). For the entire session, RR had moderate effects on RPE (RR, 5.73±1.42; TS, 6.09±1.30; p=0.307; d=0.53) and large effects on oxygen saturation (RR, 5857.4±310.0; TS, 6495.8±273.8; p=0.002, d=2.13). Therefore, RR may maintain peak torque or total work during eccentric exercise, improve oxygen utilization at the muscle, and reduce the perceived effort.